Magnesium Excretion in C. elegans Requires the Activity of the GTL-2 TRPM Channel - Teramoto, Takayuki (Public Library of Science, 2010)
Systemic magnesium homeostasis in mammals is primarily governed by the activities of the TRPM6 and TRPM7 cation channels, which mediate both uptake by the intestinal epithelial cells and reabsorption by the distal convoluted tubule cells in the kidney. In the nematode, C. elegans, intestinal magnesium uptake is dependent on the activities of the TRPM channel proteins, GON-2 and GTL-1. In this paper we provide evidence that another member of the TRPM protein family, GTL-2, acts within the C. elegans excretory cell to mediate the excretion of excess magnesium. Thus, the activity of GTL-2 balances the activities of the paralogous TRPM channel proteins, GON-2 and GTL-1.